STUDENT PLAGIARISM: CAUSES AND PREVENTION (PRACTICE OF THE SCIENTIFIC LIBRARY OF KHARKIV NATIONAL MEDICAL UNIVERSITY) - Kirichok, Irina V.; Pavlenko, Tetiana B. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article is considered the research experience of the problems of student plagiarism as the practice of academic dishonesty in the Scientific Library of Kharkiv National Medical University. The causes of this situation are analyzed, an effective means of solution to the problem are defined. The steps to create a new culture of learning and teaching in KhNMU are proposed.